Household farmers have allocated the family labour resources to their cattle farming that contribute to farmers’ income generation and distributed to their household expenditures. Household farmers face the transaction cost during the production process. The highest transaction cost, the least income allocation. The objectives of the study were (1) to develop household economy model in the corn-cattle farming system include transaction cost and (2) to analyze factors influencing the input us - Femi Hadidjah Elly; Bonar M. Sinaga; Sri Utami Kuntjoro; Nunung Kusnadi (Forum Pasca Sarjana, 2009)
Household  farmers have allocated the family labour resources to their cattle farming that contribute to farmers’ income generation and distributed to their household expenditures.  Household farmers face the transaction cost during the production process.  The highest transaction cost, the least income allocation. The objectives of the study were (1) to develop household  economy model in the corn-cattle farming system include transaction cost and (2) to analyze factors influencing the input use, output, income generation and expenditures of household farmers.  A survey was used to gather and collect information of 194 household farmers that sampling by simple random.  Simultaneous equations model with to SLS method was used to estimate the parameter.  The result showed that household economy model could describe promptly the impact of transaction cost.  The transaction cost significantly affected the farmers behavior on production decision, the use of production input and family labor as well as consumption expenditures.  A change on the policy of increasing output price, transaction costs of the cattle intermediaries and corn transport cost have affected the farmer’s household economic performances.   Key words: transaction cost, household economics, corn-cattle farming systems